2014
DOI: 10.1016/j.watres.2014.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of microalgae pre-treatments for improved anaerobic digestion: Thermal treatment, thermal hydrolysis, ultrasound and enzymatic hydrolysis

Abstract: Anaerobic digestion (AD) of microalgae is primarily inhibited by the chemical composition of their cell walls containing biopolymers able to resist bacterial degradation. Adoption of pre-treatments such as thermal, thermal hydrolysis, ultrasound and enzymatic hydrolysis have the potential to remove these inhibitory compounds and enhance biogas yields by degrading the cell wall, and releasing the intracellular algogenic organic matter (AOM). This work investigated the effect of four pre-treatments on three micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(88 citation statements)
references
References 27 publications
6
79
1
2
Order By: Relevance
“…It has become one of the feedstock for anaerobic digestion in recent years and its reported specific methane yield was within the range of 50-1197 mL/g VS (Gonzalez-Fernandez et al, 2012;Ometto et al, 2014). But due to its high nitrogen content, it may lead to ammonia toxicity (Passos et al, 2014), so it is a suitable feedstock for co-digestion with C-rich material.…”
Section: H I G H L I G H T Smentioning
confidence: 99%
“…It has become one of the feedstock for anaerobic digestion in recent years and its reported specific methane yield was within the range of 50-1197 mL/g VS (Gonzalez-Fernandez et al, 2012;Ometto et al, 2014). But due to its high nitrogen content, it may lead to ammonia toxicity (Passos et al, 2014), so it is a suitable feedstock for co-digestion with C-rich material.…”
Section: H I G H L I G H T Smentioning
confidence: 99%
“…Some promising results have already been shown in terms of biomass solubilisation and biogas production increase after enzymatic pretreatment of pure microalgae cultures (Ometto et al, 2014; pretreatment on mixed microalgal biomass grown in wastewater treatment systems. To date, results showed how the methane yield of Chlorella vulgaris was increased by 70% with cellulase (Onozuka) and a hemicellulose mix (Macerozyme) (Wieczorek et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Reference [28], the three microalgal species Scenedesmus obliquus, Chlorella sorokiniana and Arthrospira maxima were tested at five temperatures (105 • C, 120 • C, 145 • C, 155 • C, 165 • C) with two kinds of processes ((hydro-)thermal degradation and (hydro-)thermal hydrolysis with steam injection). It was concluded that the temperature was identified as the main driver of the cell wall breakage [28].…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that the temperature was identified as the main driver of the cell wall breakage [28]. It was also concluded that, for single cell algae that have carbohydrates polymers/matrix and acetolysis resistance biopolymers (algaenan) included in their cell walls (Scenedesmus obliquus, Chlorella sorokiniana), the rapid change of temperature/pressure caused by steam injection was only effective at pressures and temperatures higher than 4 bar and 150 • C respectively, while for cellulose free filamentous algae (Arthrospira maxima), lower temperature/pressure combinations were sufficient to produce cell damage [28]. This is generally in accordance with the results of this work, as S. rubescens, C. vulgaris and N. oculata (which all have an algaenan layer) have a higher increase of the lipid yield from direct to pre-treated extraction in contrast to A. platensis, which only has a small increase as the cell wall is already ruptured by freeze drying.…”
Section: Discussionmentioning
confidence: 99%